A influência da matriz sobre a borda na floresta Ombrófila aberta no nordeste do Brasil - Gonzalez, Mateus (2011)
Although the edge effect is a phenomenon much studied in tropical forests, the effects of edge creation in open ombrophylous forests of the Atlantic Forest of the northeastern Brazil are little discussed. Communities with a greater opening, including periods with partial loss of leaves may respond differently to the impacts of edge formation because the species may be more light-adapted. The matrix can have a direct influence on the edge quality. Most studies available examine the consequences of the interface between forest and agricultural areas and pasture. However, the effects of the creation of a water layer have been little studied, despite being a much frequent impact in the last century. In this study, we analyze the edge effect in two faces of a fragment, the first edge in contact with sugarcane crop, and the second with an artificial pond. To neutralize the effect of selective logging and avoid counting species established before the edge formation, we analyzed the composition and density of the juvenile layer. In the second face (oriented toward to the water layer), the distribution of species richness and density of individuals presented a relationship with the edge-interior gradient. In the area in contact with the sugarcane crop, the relationship was not significant. The results pointed out that the construction of a dam (water layer) has caused an edge effect in the Forest fragment, which seems to be not expressive in the area adjacent to sugarcane cultivation.